Estudio biótico (mastofauna) en las gradientes altitudinales de la cordillera occidental de los andes, en los bosques siempre verde montano y piemontano, en el Cantón La Maná, Provincia de Cotopaxi, Ecuador. - Limachi Maliza, Aurora Elizabeth (2024)
The present research aimed to carry out a biotic study (mastofauna) along the altitudinal gradients of the western Andes mountain range, in the montane evergreen forests and foothills in the La Maná Canton, Cotopaxi Province, Ecuador. For this purpose, information on large and small mammals was collected at three sampling points, employing various monitoring techniques. With the collected information, a qualitative and quantitative inventory of the recorded individuals was conducted, and the biodiversity index of the three sampling points was calculated, thus allowing the creation of a catalog with the identified species in the study area. It was determined that the first point recorded 76 individuals, comprising a total of 14 species, 5 orders, and 12 families. The relative abundance determined that common species had a 0% dominance, rare species 7%, less common species 21%, and abundant species 72%. The second point recorded 30 individuals, totaling 14 species, 5 orders, and 12 families. The calculation of relative abundance determined that common and rare species had 0% dominance, less common species 73%, and rare species 27%. The third point recorded 21 individuals, with a total of 10 species, 6 orders, and 10 families. Relative abundance determined that less common species were the most dominant at 45%, followed by common species at 33%, and finally, rare and abundant species at 22% and 0%, respectively.